2010
DOI: 10.1007/s00464-010-1244-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue for intraperitoneal laparoscopic mesh fixation: a comparative study in a swine model

Abstract: Mesh fixation using fibrin glue has comparable tensile strength and adhesion rate to sutures with tacks in the swine model. Increased contraction and migration rates associated with fibrin glue alone may be an issue and warrants further study. On the other hand, the GT group showed similar biomechanical characteristics to the other groups and may represent a reasonable alternative to the use of transfascial sutures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 66 publications
1
9
0
1
Order By: Relevance
“…In addition to these clinical findings, experimental studies by Erikson et al [15], Clark et al [61], Rieder et al [62], and Fortelny et al [16] verified that fibrin sealant could significantly reduce the numbers of perforating fixation devices for mesh fixation. Thus, a reduction of tissue trauma and nerve injuries could be achieved.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to these clinical findings, experimental studies by Erikson et al [15], Clark et al [61], Rieder et al [62], and Fortelny et al [16] verified that fibrin sealant could significantly reduce the numbers of perforating fixation devices for mesh fixation. Thus, a reduction of tissue trauma and nerve injuries could be achieved.…”
Section: Discussionmentioning
confidence: 86%
“…Synthetic mesh fixation in both open and laparo-endoscopic hernia repair involves a consideration of the strength of fixation versus the risk of trauma to local tissues and nerve damage through entrapment. Mesh fixation complications include: mesh migration, adhesions, erosion and hernia recurrence, 531 535 “meshoma” formation, 536 tack hernias, 537 chronic pain, 538 543 and infection. 544 , 545 A number of RCTs—also summarized in meta-analyses—have compared different mesh fixation methods in both open and laparo-endoscopic IH repair.…”
Section: Mesh Fixationmentioning
confidence: 99%
“…It is unknown whether mesh fixation with FS reduces pain after LVHR, as no clinical studies have been published. Experimental studies have shown FS to be as effective as titanium tacks for mesh fixation in LVHR in terms of strength of ingrowth and adhesion formation9, 10, but mesh dislocation has also been reported11. This randomized double‐blind trial was conducted to evaluate the effect of FS for mesh fixation in LVHR for umbilical hernia.…”
Section: Introductionmentioning
confidence: 99%